2013
DOI: 10.1007/s00429-013-0643-2
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive neuronal expression of SUCLA2 in the human brain

Abstract: SUCLA2 encodes the ATP-forming b subunit (A-SUCL-b) of succinyl-CoA ligase, an enzyme of the citric acid cycle. Mutations in SUCLA2 lead to a mitochondrial disorder manifesting as encephalomyopathy with dystonia, deafness and lesions in the basal ganglia. Despite the distinct brain pathology associated with SUCLA2 mutations, the precise localization of SUCLA2 protein has never been investigated. Here, we show that immunoreactivity of A-SUCL-b in surgical human cortical tissue samples was present exclusively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In our previous study, we identified neurons and astrocytes using the markers Nissl and GFAP/S100, respectively (Dobolyi et al 2013). In the present work we extended our investigation by including the microglial marker ionized calcium-binding adapter molecule 1 (Iba1) and oligodendroglial marker myelin basic protein.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…In our previous study, we identified neurons and astrocytes using the markers Nissl and GFAP/S100, respectively (Dobolyi et al 2013). In the present work we extended our investigation by including the microglial marker ionized calcium-binding adapter molecule 1 (Iba1) and oligodendroglial marker myelin basic protein.…”
Section: Introductionmentioning
confidence: 60%
“…We have used a new antibody directed against the human SUCLG2 protein that does not distinguish among various isoforms (see "Materials and Methods") as in (Dobolyi et al 2013). The specificity of SUCLG2 immunoreactivity was validated using human fibroblast cells, see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations